Emergence of New Language Authorities in the Digital Era: The Roles of Edtech Platforms in Arabic Language Learning: Experience from Digital Learners’ Generation in Islamic Universities - Muhammad Jabir; Nurdin Nurdin; Fatimah Saguni; Hamlan Andi Baso Mala (Universitas Negeri Makassar, 2026)
The emergence of new information technology has brought about changes in language-teaching approaches. The changes include shifting conventional language-learning knowledge to digital resources, helping university students become more independent. The phenomenon causes the emergence of new authorities in language learning. However, limited studies have examined the new language-teaching authorities and how they emerge in the digital era. This study, therefore, aims to investigate what new language teaching authorities are and how they have emerged from the perspectives of Arabic learners. Using a qualitative multiple-case study design, this study was conducted at two Islamic universities. Data were gathered through direct observation, focus group discussions, in-depth interviews, and analysis of written materials. The focus group discussions involved 20 students; 12 of them were then recruited for in-depth interviews. Data was analyzed using a thematic approach. Our findings show that EdTech platforms have played a more critical role in Arabic language teaching than traditional Arabic teachers and Arabic educational institutions. Such EdTech platforms include Arabic-language organization websites, social media platforms, and government websites for Arabic teaching. However, the most important finding of our study is that EdTech platforms have played a significant role in fostering more independent Arabic language learning, which may have reduced the roles of conventional language resources such as teachers, schools, and language laboratories. In other words, EdTech platforms outperform conventional language-teaching authorities. The emergence of new language-teaching authorities might streamline the bureaucratic process in Arabic language learning, as students might no longer be required to attend conventional language-learning settings such as schools or language laboratories. Our study contributes to the development of new approaches and the redesign of the curriculum in language teaching and learning. This study has limitations, including a focus solely on Arabic and a reliance on two case studies. Future studies might involve other languages, such as English, with more case studies to increase insight and trustworthiness.